Smoking among troops deployed in combat areas and its association with combat exposure among navy personnel in Sri Lanka - De Silva, V.A.; Jayasekera, N.E.L.W.; Hanwella, Raveen (Springer Nature, 2012)
Background: Among military personnel alcohol consumption and binge-drinking have increased but cigarette smoking has declined in the recent past. Although there is a strong association between smoking and PTSD the association between combat exposure and smoking is not clear. Methods: This cross sectional study was carried out among representative samples of SLN Special Forces and regular forces deployed in combat areas. Both Special Forces and regular forces were selected using simple random sampling. Only personnel who had served continuously in combat areas during the one year period prior to end of combat operations were included in the study. Females were not included in the sample. The study assessed several mental health outcomes as well as alcohol use, smoking and cannabis use. Sample was classified according to smoking habits as never smokers, past smokers (those who had smoked in the past but not within the past year) and current smokers (those smoking at least one cigarette within the past 12 months). Results: Sample consisted of 259 Special Forces and 412 regular navy personnel. Prevalence of current smoking was 17.9% (95% CI 14.9-20.8). Of the sample 58.4% had never smoked and 23.7% were past smokers. Prevalence of current smoking was significantly higher among Special Forces personnel compared to regular forces. (OR 1.90 (95% CI 1.20-3.02). Personnel aged ≥35 years had the lowest prevalence of smoking (14.0%). Commissioned officers had a lower prevalence (12.1%) than non commissioned officers or other ranks. After adjustment for demographic variables and service type there was significant association between smoking and combat experiences of seeing dead or wounded [OR 1.79 (95%CI 1.08-2.9)], handling dead bodies [OR 2.47(95%CI 1.6-3.81)], coming under small arms fire [OR 2.01(95%CI 1.28-3.15)] and coming under mortar, missile and artillery fire [OR 2.02 (95%CI 1.29-3.17)]. There was significant association between the number of risk events and current smoking [OR 1.22 (95%CI1.11-1.35)]. Conclusions: There was significant association between current smoking and combat experiences. Current smoking was strongly associated with current alcohol use. Prevalence of current smoking was less among military personnel than in the general population. Prevalence of smoking was significantly higher among Special Forces personnel.
Keywords: Sri Lanka; Smoking; Military personnel; War; Combat exposure